Evaluation of the social-economic impacts of hyena attacks on humans and livestock in the Nyang’whale district of Tanzania - Noela Samwel Hello; Rosemary Peter Mramba; Doreen Jeremiah Mrimi (BMC Ecology and Evolution)
Abstract Background The spotted hyena (Crocuta crocuta) is one of the carnivore species that frequently comes into conflict with humans. These conflicts are attributed to their scavenging foraging behaviour and their ability to occupy habitats close to human settlements. In Tanzania, the Geita region has recently experienced an increase in livestock and human attacks by hyenas. However, there are limited studies examining the extent of these attacks and the associated social-economic impacts. Thus, this study evaluated the social impacts and economic losses due to spotted hyena attacks in the Nyang’whale district in the Geita region. Materials and methods The study was carried out in three villages in the Nyang’whale district, namely Wavu, which is close to the Mienze Forest Reserve; Bukungu, which is far from the forest but surrounded by many hills; and Izunya, which is far from the forest and the hills. Data collection was done through household surveys, focus group discussions, and key informant interviews. A Chi-square test assessed the association between hyena fear and daily activities across villages. Poisson regression compared the number of livestock attacked by hyenas by village and species. Linear regression analysis compared financial losses due to livestock attacks and reductions in working time due to hyena fear across villages. Results There was a significant variation in the frequency of livestock and human attacks between the villages. The frequency of livestock attacks was lower in Bukungu village, but human attacks were highest in this village. The Wavu village, which is close to the forest, had the highest livestock number and attacks, but no human attacks were reported. The hyena attacks had created fear, which had changed the daily routines of the villagers. The village with the most human attacks reported a high rate of school dropouts, while the one with the most livestock attacks reported a reduction in sleeping time at night to watch livestock. Economic losses due to livestock attacks averaged $300.5 per household per year, while losses due to reduced working time were equivalent to $285.6 per household per year. Conclusion Given that villages with a large number of livestock experienced more livestock attacks and fewer human attacks, this suggests that hyenas may target humans when their food resources are limited. Therefore, conducting further studies to assess the hyena population and the availability of their natural prey is crucial for formulating effective intervention strategies. Additionally, villagers should be educated on ways to control human and livestock attacks based on the animals’ ecology and behaviour.